EFEK CHITOSAN PADA HISTOPATOLOGIS AORTA TIKUS PUTIH YANG DIBERI PAKAN LEMAK TINGGI - Isdadiyanto, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
The objective of this study was to analyze the influence of chitosan on aorta histopatologic of Sprague Dawley rats induced by high fat ration. The animals for this study were twenty adult male rats divided into four groups, i.e. group I as the control was fed with basal ration containing normal fat for 3 months, group II was fed ration containing high fat for 3 months, group III was fed ration containing high fat and given chitosan 180 mg per kg body weight per day orally in 2 ml aquadest for 3 months, group IV was fed ration containing high fat for 3 months and after 1 month given chitosan 180 mg per kg body weight per day orally in 2 ml aquadest for 2 months. Each group consisted of five animals. After 90 days, the rats were necropsied and the aortas of heart were collected to histopathological. Histopathologic analysis of aortas using hematoxylin-eosin staining method and were analysis by descriptive. The rats given normal diet did not induce atheroma plaque. The rats given high fat diet induced atheroma plaque. The rats given high fat and given chitosan simultaneously did not induce atheroma plaque. The rats given high fat and after 1 month given chitosan 40% did not induce atheroma plaque and 60% induced atheroma plaque. Based on the result of this study, it was concluded that high fat ration was a major factor able to cause atherosclerosis and chitosan was able to prevent atheroma plaque formation. Â Key words: Atherosclerosis, aorta, atheroma plaque, chitosan, high fat ration.